2020
DOI: 10.1002/bjs.11398
|View full text |Cite
|
Sign up to set email alerts
|

Effect of footplate neuromuscular electrical stimulation on functional and quality-of-life parameters in patients with peripheral artery disease: pilot, and subsequent randomized clinical trial

Abstract: Background Supervised exercise programmes for intermittent claudication have poor access and limited compliance. Neuromuscular electrical stimulation (NMES) may be an effective alternative. A proof‐of‐concept study and RCT were conducted. Methods In study 1, eligible patients underwent baseline assessment; treadmill testing for initial (ICD) and maximum (MCD) claudication distance; EuroQoL Five Dimensions five‐level instrument (EQ‐5D‐5L™) and Intermittent Claudication Questionnaire (ICQ) assessment; and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
1
17
2
Order By: Relevance
“…The device consists of electrodes for quadriceps stimulation and footplate electrodes for stimulation of the calf and foot. The footplate has previously been investigated for its influence on peripheral artery disease and chronic venous disease and was found to significantly improve circulation and walking distance 32 33. These investigations did not include quadriceps stimulation and there have been no investigations into the effects of the device for KOA.…”
Section: Introductionmentioning
confidence: 99%
“…The device consists of electrodes for quadriceps stimulation and footplate electrodes for stimulation of the calf and foot. The footplate has previously been investigated for its influence on peripheral artery disease and chronic venous disease and was found to significantly improve circulation and walking distance 32 33. These investigations did not include quadriceps stimulation and there have been no investigations into the effects of the device for KOA.…”
Section: Introductionmentioning
confidence: 99%
“…The RCT study later used the same treatment protocol and found a significant adjunctive benefit of NMES to supervised exercise program alone for ICD. The QoL survey results also improved significantly in both studies when using/applying NMES [34].…”
Section: Nmes Controversymentioning
confidence: 71%
“…23 Recent publications have asessed its use in claudicants. 38,39 Despite limitations of the pilot data, mainly pertaining the small sample size, the positive results compared to a sham device were encouraging. Previous work has suggested that graduated compression stockings (GCS) worn for 6 hours have a significantly larger effect on limb volume compared to this NMES device (a single session of 30 minutes of treatment).…”
Section: Introductionmentioning
confidence: 96%